Influence of drying methods on the bioactive compound and antioxidant activity of pomelo residue - Abd Rahman, Nur Farhana; Shamsudin, Rosnah; Ismail, Amin; Abdul Karim Shah, Nor Nadiah; Varith, J. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Pomelo (Citrus grandis L. Osbeck) fruit is a rich source of bioactive compound incorporating outstanding antioxidant properties. However, the pomelo residue known as pulp waste is usually discarded after the juice has been extracted. Pomelo residue is extremely perishable which simultaneously leads to difficulty of handling, processing and transporting due to its high moisture content. Thus, pomelo residue needs dehydration process to remove the moisture and preserve the bioactive compounds. Therefore, the effect of the method used for drying on the bioactive compound and antioxidant activities of pomelo residue was investigated by three different methods of drying: freeze (control), conventional and vacuum drying. Antioxidant includes total phenolic content (TPC) whereas its activities were indicated by using ferric reducing antioxidant potential (FRAP) and 2, 2- diphenyl-1-picrylhydrazyl (DPPH) scavenging activity. Bioactive compound known as total phenolic content (TPC) showed significant increased (p<0.05) in the overall temperature of conventional drying method whereas vacuum drying showed no significant difference. In addition, reduction of DPPH was observed in both drying methods (conventional and vacuum dried) in contrast with FRAP, no significant difference (p>0.05) was observed in conventional drying. In conclusion, this study concludes supportive proof for the superiority oven dried pulp waste of Citrus grandis L. Osbeck showed a potentially excellent source of the bioactive compound and could be exploited as functional ingredients in the nutraceutical field.